Cumulus cells steroidogenesis is influenced by the degree of oocyte maturation - Barboni Barbara; Turriani Maura; Bernabò Nicola; Lucidi Pia; Mattioli Mauro (BMC, 2003)
Abstract Background The possibility to predict the ability of a germ cell to properly sustain embryo development in vitro or in vivo as early as possible is undoubtedly the main problem of reproductive technologies. To date, only the achievement of nuclear maturation and cumulus expansion is feasible, as all the studies on cytoplasmic maturation are too invasive and have been complicated by the death of the cells analyzed. The authors studied the possibility to test the cytoplasmic quality of pig oocytes by evaluating their ability to produce steroidogenesis enabling factor(s). To this aim, oocytes matured under different culture conditions that allowed to obtain gradable level of cytoplasmic maturation, were used to produce conditioned media (OCM). The secretion of the factor(s) in conditioned media was then recorded by evaluating the ability of the spent media to direct granulosa cells (GC) steroidogenesis. Methods In order to obtain germ cells characterized by a different degree of developmental competence, selected pig oocytes from prepubertal gilts ovaries were cultured under different IVM protocols; part of the matured oocytes were used to produce OCM, while those remaining were submitted to in vitro fertilization trials to confirm their ability to sustain male pronuclear decondensation. The OCM collected were finally used on cumulus cells grown as monolayers for 5 days. The demonstration that oocytes secreted factor(s) can influence GC steroidogenesis in the pig was confirmed in our lab by studying E2 and P4 production by cumulus cells monolayers using a radioimmunoassay technique. Results Monolayers obtained by growing GC surrounding the oocytes for five days represent a tool, which is practical, stable and available in most laboratories; by using this bioassay, we detected the antiluteal effect of immature oocytes, and for the first time, demonstrated that properly matured germ cells are able to direct cumulus cells steroidogenesis by inhibiting E2 production (P < 0.01). Nevertheless, only fully competent oocytes were able to suppress estrogens production, while those cultured under unfavourable conditions were unable to exert any inhibitory effect on the functions of cumulus cells (P < 0.01). Conclusion These results demonstrated that good quality oocytes can be easily selected on the basis of their ability to affect granulosa cell steroidogenesis thus reducing failures in reproductive technologies due to the transfer of fertilized oocytes with a scarce ability to sustain embryo development.